(untitled) - Brown, James Dean (Cambridge [England], 1988)
This text focuses on the skills and processes necessary for understanding statistical research in language learning Designed for language teachers with no previous background in statistics, the paperback edition focuses on the skills and processes necessary for understanding statistical research in language learning. Brown explains the basic terms of statistics, the structure and organization of statistical research reports, the system of statistical logic, and how to decipher tables, charts, and graphs
Luận văn tốt nghiệp - Tiếng Anh,Tiểu luận tốt nghiệp - Tiếng Anh,Thu thập và phân tích dữ liệu trong nghiên cứu giáo dục tiếng Anh
Keywords: Second language acquisition,Thu nhận ngôn ngữ thứ hai; Statistical methods,Phương pháp thống kê